Malolactic fermentation of wines with immobilised lactic acid bacteria : Influence of concentration, type of support material and storage conditions - Genisheva, Zlatina Asenova (2013)
Corn cobs, grape skins and grape stems were evaluated as support materials for immobilization of the lactic acid bacteria Oenococcus oeni. The support materials with immobilized cells were further used in malolactic fermentation (MLF) of white wine. Viability of using the immobilized supports was evaluated in consecutive batch fermentations under different conditions of temperature, ethanol and SO2. Additionally, the possibility of storage and operational stability of the immobilized supports was also studied. All the three supports presented large potential for immobilization of O. oeni cells. The consecutive batches of MLF were successfully conducted for a total period of around 5 months with the possibility of storage of the biocatalyst for 30 d in wine at 25 °C.